The strange case of the patriarchs in Jeremaiah 33:26 - C. Lombaard (Acta Theologica)
Jeremiah 33:26 presents a number of interpretational questions, including the relationship of the Jeremiah 33:23-26 pericope with its textual surroundings; the compositional integrity of this pericope; the possible intentions of this passage, and the curious reference to the patriarchs – also with the name of Isaac spelt unusually. The unexpected reference to the patriarchs, in this instance, is of particular concern, since it has direct bearing on a new understanding of the patriarchs in history and text that the author has been developing. Why would the Old Testament patriarchs, so rarely referred to outside the Pentateuch, surface in this particular prophetic text? This article explores these issues, also as they relate to the author’s theory-indevelopment on the patriarchs of Israel.